2002
DOI: 10.3354/dao048213
|View full text |Cite
|
Sign up to set email alerts
|

Production of polyclonal antibodies to Batrachochytrium dendrobatidis and their use in an immunoperoxidase test for chytridiomycosis in amphibians

Abstract: Polyclonal antibodies were produced for diagnosing chytridiomycosis in amphibians. Two sheep and 4 rabbits were inoculated with homogenized whole culture of Batrachochytrium dendrobatidis in Freund's complete adjuvant or triple adjuvant. Antisera from all animals reacted strongly with all stages of B. dendrobatidis and stained the walls, cytoplasm, rhizoids and zoospores in an indirect immunoperoxidase test. Significant cross-reactivity occurred only with some fungi in the Chytridiomycota, and there are no mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 11 publications
2
63
0
Order By: Relevance
“…Rhizoids were rarely seen in skin sections examined by electron microscopy. They could not be seen in haematoxylin and eosin stained histology sections, but were discernible adjacent to sporangia when stained with the immunoperoxidase stain (Berger et al 2002). The fungi are often found in clusters on skin, 57…”
Section: Batrachochytrium Dendrobatidis In Skinmentioning
confidence: 99%
“…Rhizoids were rarely seen in skin sections examined by electron microscopy. They could not be seen in haematoxylin and eosin stained histology sections, but were discernible adjacent to sporangia when stained with the immunoperoxidase stain (Berger et al 2002). The fungi are often found in clusters on skin, 57…”
Section: Batrachochytrium Dendrobatidis In Skinmentioning
confidence: 99%
“…Histological and immunohistochemical analyses were conducted on the tadpole of L. hasseltii following the methods of Berger et al (2000) and Hyatt et al (2007), respectively. The immunoperoxidase stain employed rabbit 667 anti-Bd polyclonal antibody (Berger et al 2002). …”
Section: Methodsmentioning
confidence: 99%
“…However, disease surveys to date have been severely limited by the shortcomings of available diagnostic techniques, which until very recently have been: (1) insensitive, yielding many false-negatives (Berger et al 2002; (2) non-specific, leaving open the possibility for false-positives and observer bias; (3) invasive, requiring a skin sample such as webbing or toes (Berger et al 2002, Lips et al 2003; and (4) timeconsuming. While it has been suggested that chytridiomycosis in severely infected postmetamorphic individuals can be easily diagnosed by the presence of abnormal epidermal sloughing, reddening of the ventral surfaces, and behavioral changes such as lethargy and loss of righting reflex (Berger et al 1999a), animals at these later stages of infection are rarely found in the wild, due both to the short time span over which they are likely to survive, and the high rate at which they are scavenged (Green et al 2002).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Sensitivity and specificity of this technique has been improved slightly by the use of polyclonal antibodies and immunoperoxidase (IPX) staining (Berger et al 2002), but even this method may fail to detect a large proportion of infected animals ). More recently, a co-localisation technique ) has been designed to stain both Batrachochytrium dendrobatidis and the keratinized epidermis that the fungus infects, but no experiments have been undertaken to quantify the sensitivity of this technique.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%